Analyzing the impacts of cadmium alone and in co-existence with polypropylene microplastics on wheat growth - Han, Zhiwei; Osman, Raheel; Liu, Yi; Wei, Zhangdong; Wang, Lin; Xu, Ming (Frontiers in Plant Science, 2023)
Heavy metals typically coexist with microplastics (MPs) in terrestrial ecosystems. Yet, little is known about how the co-existence of heavy metals and MPs affect crops. Therefore, this study aimed to evaluate the impact of cadmium (Cd; 40 mg/L) alone and its co-existence with polypropylene (PP)-MPs (50 and 100 µm) on seed germination, root and shoot growth, seedling dry weight (DW), and antioxidant enzyme activities of wheat. The study demonstrated that the germination rate of wheat did not vary significantly across treatment groups. Yet, the inhibitory impact on wheat seed germination was strengthened under the co-existence of Cd and PP-MPs, as the effect of a single treatment on seed germination was non-significant. The germination index and mean germination time of wheat seeds were not affected by single or combined toxicity of Cd and PP-MPs. In contrast, Cd and PP-MPs showed synergistic effects on germination energy. Wheat root and shoot length were impeded by Cd alone and in combination with PP-MPs treatments. The DW of wheat seedlings showed significant change across treatment groups until the third day, but on the seventh day, marginal differences were observed. For example, on third day, the DW of the Cd treatment group increased by 6.9% compared to CK, whereas the DW of the 100 µm PP-MPs+Cd treatment group decreased by 8.4% compared to CK. The co-occurrence of Cd and PP-MPs indicated that 50 μm PP-MPs+Cd had an antagonistic impact on wheat seedling growth, whereas 100 μm PP-MPs+Cd had a synergistic impact due to the larger size of PP-MPs. The antioxidant enzyme system of wheat seeds and seedlings increased under single Cd pollution, while the activities of superoxide dismutase, catalase, and peroxidase were decreased under combined pollution. Our study found that Cd adversely affects wheat germination and growth, while the co-existence of Cd and PP-MPs have antagonistic and synergistic effects depending on the size of the PP-MPs.